The Influence of Principal Leadership, Teacher Competence, and School Culture on Job Satisfaction and Its Implications for Teacher Performance - Rudiatna, R Dudi; Affandi, Azhar; Rusyani, Erni (Almana : Jurnal Manajemen dan Bisnis, 2025)
Improving educational quality in vocational schools requires effective leadership, competent teachers, and a positive school culture, as these factors shape teachers’ job satisfaction and performance. This study aims to analyze the influence of principal leadership, teacher competence, and school culture on teacher job satisfaction and its implications for teacher performance in public vocational high schools (SMK) across Greater Bandung, West Java. Using a descriptive and verifiable quantitative design with path analysis, the study involved 39 public SMKs and collected data through questionnaires administered using proportional stratified random sampling, resulting in a sample of 351 teachers. The findings show that principal leadership, teacher competence, and school culture are perceived as quite effective, good, and strong, respectively, while teacher job satisfaction and performance fall into the fairly high category. Path analysis indicates that principal leadership, teacher competence, and school culture each have a positive and significant effect on teacher job satisfaction. Furthermore, teacher job satisfaction positively and significantly influences teacher performance. These results imply that strengthening leadership, enhancing teacher competence, and cultivating a supportive school culture can meaningfully increase teacher job satisfaction, which subsequently improves teacher performance and contributes to sustained educational quality improvement.